THE USE OF DICTATION-COMPOSITION TECHNIQUE TO DECREASE STUDENTS’ ERRORS IN WRITING (AN EXPERIMENTAL RESEARCH FOR THE FIRST GRADE STUDENTS AT SMA NEGERI 4 BANDA ACEH) - Mulyani; Rosdiana; Diva Aulia (Jurnal Metamorfosa, 2019)
Penelitian ini menerangkan tentang penggunaan teknik mendikte-mengarang (dictation-composition)untuk mengurangi kesalahan siswa dalam menulis. Tujuan dari penelitian ini adalah untuk mencari kesalahan yang paling banyak dilakukan oleh siswa setelah dictation-compositionditerapkan dan untuk mengetahui apakah teknik tersebut dapat mengurangi kesalahan siswa dalam menulis atau tidak. Penelitian ini adalah penelitian kuantitatif dimana data penelitian diperoleh dengan menggunakan tes dan dokumentasi tes menulis siswa. Objek dari penelitian ini adalah siswa kelas I SMA Negeri 4 Banda Aceh. Berdasarkan data dari dokumentasi tes menulis siswa, kesalahan yang paling banyak dilakukan oleh siswa setelah dictation-compositiondilaksanakan adalah kesalahan tata bahasa dengan total persentase data adalah 46,42%. Sementara itu, data dari tes dianalisis dan dihitung dengan menggunakan rumus statistik. Hasil dari tes menunjukkan bahwa skor rata-rata pre-test adalah 38.80, sedangkan skor rata-rata post-test adalah 40.61. Selanjutnya, hasil dari t-test = 2.12 dan t-table = 1.70. Ini membuktikan bahwa skor t-test lebih tinggi daripada t-tabel, sehingga hipotesis alternatif (Ha) diterima dan hipotesis nol (Ho) ditolak. Abstract This research reports an investigation of the use of dictation-composition to decrease students’ errors in writing. The objectives of this study are to determine the most errors made by the students after the dictation-composition implemented, and to find out whether dictation-composition technique decreases the students’ errors in writing or not. The research was conducted by using quantitative research and the data was collected using test and documentation of students' writing test. The object of this research was the students at the first grade of SMA Negeri 4 Banda Aceh. Based on the data from documentation of students' writing test, it showed that the most errors made by the students after the dictation-composition implemented was in grammatical errors with the total of data percentage is 46.42%. Meanwhile, the data from test was analyzed and calculated by the statistical formula. It showed that the mean score of pre-test was 38.80, while the mean score of post-test was 40.61. Furthermore, the result was showed that t-test = 2.12 and t-table = 1.70. It means that t-test score was higher than t-table, so the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. Keywords: Dictation-Composition Technique, Descriptive Text, Errors, Writing